1988
DOI: 10.1242/jeb.135.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Estimates of Body Drag of Large Waterfowl and Raptors

Abstract: To whom reprint requests should be addressed. Measurements of the body frontal area of some large living waterfowl (Anatidae) and raptors (Falconiformes) were found to vary with the two-thirds power of the body mass, with no distinction between the two groups. Wind tunnel measurements on frozen bodies gave drag coefficients ranging from 0.25 to 0.39, in the Reynolds number range 145 000 to 462 000. Combining these observations with those of Prior (1984), which extended to lower Reynolds numbers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The bird’s aerodynamic power output implies a tangential aerodynamic thrust force T = P ⁄ V , where V is the bird’s airspeed neglecting any induced velocity component. We model the opposing aerodynamic drag as where ρ = 1.23 kg m −3 is air density and where S b = 0.00813 m 2/3 is an empirical scaling relationship 47 modelling body frontal area S b as a function of body mass m . Here b is wingspan and S is wing area, both of which are assumed to be maximal throughout the manoeuvre (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The bird’s aerodynamic power output implies a tangential aerodynamic thrust force T = P ⁄ V , where V is the bird’s airspeed neglecting any induced velocity component. We model the opposing aerodynamic drag as where ρ = 1.23 kg m −3 is air density and where S b = 0.00813 m 2/3 is an empirical scaling relationship 47 modelling body frontal area S b as a function of body mass m . Here b is wingspan and S is wing area, both of which are assumed to be maximal throughout the manoeuvre (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Every reduction in drag or increase in lift can therefore improve the flight efficiency of a bird. Larger wing surfaces, for example, can increase lift (Tobalske 2007), while a streamlined body reduces drag (Pennycuick et al 1988). Recent studies have suggested that wing surface heating under solar radiation could affect the lift-to-drag ratio of a flying bird and that this effect would be stronger in hotter, dark-winged birds (Hassanalian et al 2017, 2018a, 2018b, Rogalla et al 2019.…”
Section: Thermal Effects Of Wing Coloration On Flight Performancementioning
confidence: 99%
“…This depends on the morphology of the bird and the Reynolds number Re according to with S b and FR t are respectively the frontal area of the body and the fitness ratio of the bird, and both of them can be estimated from other allometric formulas i.e. [20, 21]. The Reynolds number is calculated with the reference length of the mean aerodynamic chord , with µ being the dynamic viscosity.…”
Section: Dynamical Model Of Bird Flightmentioning
confidence: 99%
“…with S b and FR t are respectively the frontal area of the body and the fitness ratio of the bird, and both of them can be estimated from other allometric formulas i.e. [20,21].…”
Section: Drag Production By Body and Wingmentioning
confidence: 99%